CONSULTATION OF WORKERS AS A MEASURE FOR IMPROVEMENT THE OH&S MANAGEMENT SYSTEM. CASE STUDY AT THE „VASILE ALECSANDRI” UNIVERSITY OF BACAU - MARIA-CRINA RADU (Journal of Engineering Studies and Research)
Identifying and assessing occupational health and safety risks and implementing measures to prevent accidents at work and occupational diseases are legal obligations and the implementation and certification of an occupational health and safety (OH&S) management system may help organization to achieve these goals, being also a credible evidence of its commitment to protect life and health of its interested parties. Consultation and participation of workers at all applicable levels and functions is part of the system; workers involved in daily activities and those most at risk can provide a broad perspective on potential problems and the decisions made with these workers are likely to be more effective for system improvement. The paper presents the results of a study on consulting workers of the "Vasile Alecsandri" University of Bacau on occupational health and safety issues.